2006
DOI: 10.1007/s00268-006-0211-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Lymph Node Metastasis of Thyroid Papillary Carcinoma Located in One Lobe

Abstract: Central node metastasis independently predicts a worse DFS for patients with papillary carcinoma larger than 1 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
126
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 23 publications
9
126
2
2
Order By: Relevance
“…A previous study (23) even suggested that patients without high-risk factors of thyroid carcinoma should not immediately undergo surgery. Neck lymph node metastasis does not affect the PTMC prognosis (24), even with re-operation following recurrence. A previous study (25) reported that the recurrence during prophylactic neck lymph nodes dissection is higher compared to those not undergoing surgery.…”
Section: Discussionmentioning
confidence: 90%
“…A previous study (23) even suggested that patients without high-risk factors of thyroid carcinoma should not immediately undergo surgery. Neck lymph node metastasis does not affect the PTMC prognosis (24), even with re-operation following recurrence. A previous study (25) reported that the recurrence during prophylactic neck lymph nodes dissection is higher compared to those not undergoing surgery.…”
Section: Discussionmentioning
confidence: 90%
“…Also, these patients are more likely to have lateral LN metastases. Initial CND prevents central recurrence of the malignant disease [25][26][27]. Re-operations in central compartment, in comparison to initial surgery, more often lead to persistent hypoparathyroidism and RLN injury [16,[28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…node metastasis (undetectable on imaging studies but detectable on pathological examination) increased with tumor size [20][21][22]. Other research groups have investigated the relationship between lymph node metastasis and patient age.…”
Section: Prognostic Significance Of Age In Clinical Ptcmentioning
confidence: 99%